استخدام وسائل أنتشور.ف.م في تعليم اللغة العربية/The Use of Anchor.fm Based Arabic Learning Media - Nahdliyyatul Azimah; Abdul Wahid Salleh; M Imam Fakhrurrozi; Shiddiq Billal Yusuf (UIN ANTASARI, 2023)
Learning Arabic today cannot be separated from digital media. One digital platform in the form of audio that is close to the lives of millennials and has principles of efficiency in learning is Anchor.fm. a digital media in the form of audio streaming that is used by students in accessing learning materials and at the same time functions as an assignment portfolio. This article aims to describe the use of the Anchor.fm application. in Arabic learning activities and student perceptions in using the Anchor.fm application. This study is classified as qualitative-descriptive. Data collection techniques were carried out through interviews, documentation, and observation. The data analysis refers to Miles & Huberman, including; data collection, data reduction, data presentation, and conclusion. The findings obtained in this study include (1) Anchor.fm. is the main supporting medium for students to understand MSA (Modern Standard Arabic) material, for example; vocabulary pronunciation, reading narrative texts and dialogues, and understanding Arabic grammar. (2) Anchor.fm. as an efficient learning medium, from the aspect of time, effort, and cost. (3) Students are greatly helped by the existence of Anchor.fm. mainly those who come from public schools and are still beginner Arabic learners.